The Implementation of Deep Learning and Cross-Disciplinary Learning Approaches in EFL Material “Procedure Text” at Elementary School - Wibisono Yudhi Kurniawan; Rudi Hartono; Yuliati Yuliati (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the implementation of interdisciplinary learning in English language instruction on procedural texts among sixth-grade students at SD Negeri 2 Kentengsari and to explore its impact on students’ understanding and classroom engagement. A qualitative descriptive approach was employed, involving sixth-grade teachers and students as the research participants. Data were collected through classroom observations, semi-structured interviews, and documentation, then analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The credibility of the findings was ensured through source and technique triangulation. The results indicate that integrating English with Fine Arts created a more contextual, meaningful, and engaging learning environment. Students not only developed a better understanding of procedural text structures but also applied their knowledge through practical classroom activities. The interdisciplinary approach also enhanced students’ participation, collaboration, critical thinking, creativity, and artistic expression throughout the learning process. Furthermore, the teacher’s role as a facilitator was essential in guiding learning activities effectively. These findings suggest that interdisciplinary learning is an innovative instructional approach that supports holistic competency development and promotes meaningful learning experiences at the elementary school level.